Design of brake failure control on motorcycle disc brakes through an integrated cooling system - Khatami, Mokhammad; Muslim, Zulfa Adi; Kurniawan, Yuda Junaedi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
The increasing number of traffic accidents is a challenge for driver safety. The biggest factor in traffic accidents in terms of vehicles, one of which is brake failure. The number of cases of failed brakes was 7,083 cases and increased in the following year by 32% or 9,333 cases. The main cause of brake failure is the temperature condition in the brake calipers which overheats, triggering the occurrence of brake vapour lock. So, there is an urgent need for innovative solutions that can overcome the failure of the brakes on motorcycles due to the lack of effectiveness of the cooling system in the callipers. This study aimed to analyze the effectiveness of E-BRACE (electronic brake cooling control system) in preventing brake failure and to describe the design and innovation of E-BRACE as a technology for controlling brake failure through an integrated cooling system. The research was experimentally carried out with functionality tests to describe the effectiveness of E-BRACE. The test revealed that E-BRACE was very effective in stabilizing the temperature in the 9th to 15th-minute range. The highest E-BRACE effectiveness in the 15th minute is 55 %.